The impact of optical excitation on the binding in complexes of the cationic gold dimer: Au2+N2 and Au2+N2O - Förstel, M; Nahvi, N-N; Pollow, K; Green, A; Mackenzie, SR (Scientific Research Publishing, 2022)
The vibrationally resolved Ã2Σ+ ← X2Σ+ transitions of Au+2N2 and Au+2N2O are reported together with a detailed characterization of important geometric and electronic properties, enabling a deep understanding of the bonding mechanism at the molecular level. Comparison with time-dependent density functional theory calculations reveals that the ligand stabilizes the Au+2 entity in the X2Σ+ state by donating electron density into the half-filled bonding orbital leading to the strengthening of the Au-Au, N-N and N-O bonds. This effect is reversed in the Ã2Σ+ state, where the Au-Au bonding orbital is already filled and the ligand destabilizes the Au-Au bond by donating into the antibonding orbitals of Au+2. The spectral detail obtained provides a deep understanding of the interplay of multiple electronic states in gas-phase metal-complex cations, opening the door for a systematic approach in the study of excited state reactivity in organometallic chemistry.